Clinical and Functional Genetic Characterization of the Role of Cardiac Calcium Channel Variants in the Early Repolarization Syndrome - Chen, Xiu; Barajas-Martínez, Hector; Xia, Hao; Zhang, Zhonghe; Chen, Ganxiao; Yang, Bo; Jiang, Hong; Antzelevitch, Charles; Hu, Dan (Frontiers in Cardiovascular Medicine, 2021)
Background: Early repolarization syndrome (ERS) is an inherited sudden cardiac death (SCD) syndrome. The present study investigates the role of genetic variants in cardiac calcium-channel genes in the pathogenesis of ERS and probes the underlying mechanisms. Methods: Polymerase chain reaction–based next-generation sequencing was carried out using a targeted gene approach. Unrelated ERS probands carrying calcium-channel variants were evaluated clinically and compared with matched healthy controls. Wild-type (WT) and mutant CACNA1C genes were coexpressed with CACNB2b and CACNA2D1 in HEK293 cells and studied using whole-cell patch-clamp techniques and confocal fluorescence microscope. Results: Among 104 ERS probands, 16 carried pathogenic variants in calcium-channel genes (32.2 ± 14.6 years old, 87.5% male). The symptoms at diagnosis included syncope (56.3%), ventricular tachycardia/fibrillation (62.5%), and SCD (56.3%). Three cases (18.8%) had a family history of SCD or syncope. Eight patients (50.0%) had a single calcium gene rare variant. The other half carried rare variants in other ERS-susceptible genes. Compared with controls, the heart rate was slower (72.7 ± 8.9 vs. 65.6 ± 16.1 beats/min, *p < 0.05), QTc interval was shorter (408.2 ± 21.4 vs. 386.8 ± 16.9 ms, **p < 0.01), and Tp-e/QT was longer (0.22 ± 0.05 vs. 0.28 ± 0.04, ***p < 0.001) in single calcium mutation carriers. Electrophysiological analysis of one mutation, CACNA1C-P817S (c.2449C>T), revealed that the density of whole-cell calcium current (ICa) was reduced by ~84.61% compared to WT (−3.17 ± 2.53 vs. −20.59 ± 3.60 pA/pF, n = 11 and 15, respectively, **p < 0.01). Heterozygous expression of mutant channels was associated with a 51.35% reduction of ICa. Steady-state inactivation was shifted to more negative potentials and significantly accelerated as well. Confocal microscopy revealed trafficking impairment of CACNA1C-P817S (peripheral/central intensity: 0.94 ± 0.10 in WT vs. 0.33 ± 0.12 in P817S, n = 10 and 9, respectively, **p < 0.01). Conclusions: ERS associated with loss-of-function (LOF) genetic defects in genes encoding the cardiac calcium channel represents a unique clinical entity characterized by decreased heart rate and QTc, as well as increased transmural dispersion of repolarization. In the case of CACNA1C-P817S, impaired trafficking of the channel to the membrane contributes to the LOF.